STUDI EFEKTIVITAS PEMBELAJARAN SISTEM BLOK PADA MATA PELAJARAN PRODUKTIF TEKNIK PEMESINAN - Diya Zalfa Aisyah Safitri; Denny Aji Firmanta; Frendy Nur Setyawan; Garindo Prayitno; Hendri Aldi Puswadi; Ilham Agum Fitra Anggesa; Chandra Denny Kurniawan Putra; Suharno Suharno (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2024)
This study evaluates the effectiveness of the block system learning in the productive subject of Machining Engineering at SMK Negeri 5 Surakarta. Utilizing a qualitative approach, the research findings indicate that the implementation of the block system enhances student engagement, deepens theoretical understanding, and improves practical skills. Interview analyses and case studies highlight a shift from a teacher-centered to a more participatory learning approach. Positive implications of constructivist and competency-based learning are evident in the enhanced quality of learning outcomes. The conclusion emphasizes the effectiveness of the block system learning as a relevant vocational education model aligned with industry needs. Recommendations include the development of teaching methods, increased industry involvement, and further research. Gratitude is extended to SMK Negeri 5 Surakarta, educators, students, and supporters who contributed to this research.